New records of Corixidae (Heteroptera) from northeastern USA and eastern Canada, with one new synonymy - Jansson, Antti (Entomologica Fennica, 2002)
The following numbers of new state and province records of Corixidae are reported: Maine 18, New Hampshire 27, Vermont 32, Massachusetts 11, Connecticut 23, Rhode Island 22, New York 12, Ontario 9, Quebec 4, New Brunswick 3, Nova Scotia 22, Prince Edward Island 6, Newfoundland 2, and Labrador 7. Trichocorixa verticalis fenestrata Walley is synonymised with the nominate subspecies.